ЎЗБЕК АРХЕОЛОГ ОЛИМИ АҲМАДАЛИ АСҚАРОВ ИЖОДИДА БРОНЗА ДАВРИ ЎТРОҚ ДЕҲҚОНЧИЛИК МАДАНИЯТИНИНГ ЎРНИ - Каримова Д. О. (TARIXIY TADQIQOTLAR, 2025)
This article will focus on the study of cultures created by communities of agricultural culture of the Bronze Age in the scientific activity of the famous Uzbek scientist-archaeologist, academician Akhmadali Askarov. The Sapalli culture, studied by the scientist and entered into history, serves as an important source of information about the historical processes of the Bronze Age.